2015
DOI: 10.3899/jrheum.150057
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Tuberculosis in Patients with Rheumatoid Arthritis Treated with Tumor Necrosis Factor-α Antagonist: A Metaanalysis of Both Randomized Controlled Trials and Registry/Cohort Studies

Abstract: This study demonstrated a significant increase in TB risk in patients with RA treated with TNF-α antagonists; among them, ETN is least likely to cause active TB. The study also proposes the necessity of LTBI prophylaxis in patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 28 publications
5
57
1
1
Order By: Relevance
“…This finding was comparable to the result of a meta-analysis of randomized controlled trials and registry/cohort studies [10]. The risk of TB infection in ETN users has been demonstrated to be lower than that in patients taking monoclonal antibodies to TNF [13, 23, 27].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding was comparable to the result of a meta-analysis of randomized controlled trials and registry/cohort studies [10]. The risk of TB infection in ETN users has been demonstrated to be lower than that in patients taking monoclonal antibodies to TNF [13, 23, 27].…”
Section: Discussionsupporting
confidence: 82%
“…Tumor necrosis factor (TNF) plays a key role in the immunity against TB [9]. In recent years, the use of a TNF inhibitor (TNFi) in RA patients further increased the TB risk [7, 1012]. Furthermore, prior studies have shown that monoclonal antibodies to TNF, such as infliximab (IFX) and adalimumab (ADA), may drive higher TB risk than TNF receptor blockers such as etanercept (ETN) [10, 13].…”
Section: Introductionmentioning
confidence: 99%
“…53 One study estimated that preventive treatment in patients with LTBI can reduce the risk of reactivation by 65% 10. Some countries have formulated national guidelines to deal with LTBI before anti-TNF agents treatment 54.…”
Section: Discussionmentioning
confidence: 99%
“…Although their therapeutic efficacy has been confirmed, the side effects of these TNF-α antagonists need to be considered carefully in clinical practice 8. An increased risk of tuberculosis (TB) among patients receiving TNF-α antagonists has been observed,9 and several meta-analyses have evaluated the risk of TB in patients treated with TNF-α antagonists or with specific conditions 10–13. Nevertheless, the association between TNF-α antagonists and an increased risk of TB remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Although the numbers were small for comparison, this study confirmed prior data showing the lowest risk occurred among those exposed to ETN versus ADA or IFX. A meta-analysis of randomized trials and registry/cohort studies essentially confirmed these findings [15].…”
Section: Introductionmentioning
confidence: 64%